Determining The Levels of Depression and Hope in Elderly Individuals - Esra BEKİRCAN; Ayşe OKANLI (Yaşlı Sorunları Araştırma Derneği, 2023)
This study was conducted as a descriptive study to determine the depression and hopelessness levels of elderly individuals. While the population of the study consists of 150 old people who are members of one of the groups that serve retirees, the sample consists of 100 elderly people who match the study's inclusion requirements. The Sociodemographic Information Form, Geriatric Depression Scale-Short Form (GDS-15), and Beck Hopelessness Scale (BDS) were used to collect data. The research findings were gathered through face-to-face interviews between March and April 2023. In the analysis of the data, the relationships between the variables were analyzed using the Independent Sample t-Test, and the One-way ANOVA and Pearson correlation tests in the comparison of more than two independent groups. The older persons enrolled in this study had a mean GDS-15 score of 7.272.91 and a mean BIS score of 11.615.14. It was determined that older people suffered from mild depression and significant despair. The GDS-15 and BAI scores of the elderly were shown to have a strong positive (r=0.638) and statistically significant (p<0.001) connection. It was shown that the older persons who retired as employees had a greater average of sadness (7.902.69) and despair (12.584.78) than tradesmen and housewives. The mean BAI of men (12.634.87) was found to be substantially greater than the mean of women (8.564.80) (p=0.000). It is advised to conduct frequent follow-ups and raise awareness of de-pressed symptoms and hope in senior people in order to diagnose depression more readily in old age.